Designing Virtual World for Helping Students - Xiaoying Ma; Eva Xu (CV TOPAZART, 2022)
Students in Informatics are often required to work in a team environment to complete assignments. For example, in the Game Programming course, we expect students to complete a series of design projects that end with a complete game design. Classroom time is set aside each week for teams, but students need time to finish their work outside the classroom. To help them with this process and teach them effective team strategies that they can apply to their careers, we’ve created a supportive online environment. This paper will present the design created for this course and discuss the challenges and opportunities we experienced with building and deploying it.